arctan(x) - arctan(y) = arctan($$\frac{x - y}{1 + xy}$$)

We will learn how to prove the property of the inverse trigonometric function arctan(x) - arctan(y) = arctan($$\frac{x - y}{1 + xy}$$) (i.e., tan$$^{-1}$$ x - tan$$^{-1}$$ y = tan$$^{-1}$$ ($$\frac{x - y}{1 + xy}$$))

Proof:

Let, tan$$^{-1}$$ x = α and tan$$^{-1}$$ y = β

From tan$$^{-1}$$ x = α we get,

x = tan α

and from tan$$^{-1}$$ y = β we get,

y = tan β

Now, tan (α - β) = ($$\frac{tan α - tan β}{1 + tan α tan β}$$)

tan (α - β) = $$\frac{x - y}{1 + xy}$$

⇒ α - β = tan$$^{-1}$$ ($$\frac{x - y}{1 + xy}$$)

⇒ tan$$^{-1}$$ x - tan$$^{-1}$$ y = tan$$^{-1}$$ ($$\frac{x - y}{1 + xy}$$)

Therefore, tan$$^{-1}$$ x - tan$$^{-1}$$ y = tan$$^{-1}$$ ($$\frac{x - y}{1 + xy}$$)

Solved examples on property of inverse circular function arctan(x) - arctan(y) = arctan($$\frac{x - y}{1 + xy}$$)

Solve the inverse trigonometric function: 3 tan$$^{-1}$$  1/2 + √3 - tan$$^{-1}$$ 1/x = tan$$^{-1}$$ 1/3

Solution:

We know that, tan 15° = tan (45° - 30°)

⇒ tan 15° = $$\frac{tan 45° - tan 30°}{1 + tan 45° tan 30°}$$

⇒ tan 15° = $$\frac{1 - \frac{1}{√3}}{1 + \frac{1}{√3}}$$

⇒ tan 15° = $$\frac{√3 - 1}{√3 + 1}$$

⇒ tan 15° = $$\frac{(√3 - 1)(√3 + 1)}{(√3 + 1)(√3 + 1)}$$

⇒ tan 15° = $$\frac{3 - 1}{4 + 2√3}$$

⇒ tan 15° = $$\frac{1}{2 + √3}$$

⇒ tan$$^{-1}$$ ($$\frac{1}{2 + √3}$$) = 15°

⇒ tan$$^{-1}$$ ($$\frac{1}{2 + √3}$$) = $$\frac{π}{12}$$

Therefore, from the given equation we get,

3 tan$$^{-1}$$ $$\frac{1}{2 + √3}$$ - tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ $$\frac{1}{3}$$

⇒ 3 · $$\frac{π}{12}$$ - tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ $$\frac{1}{3}$$

⇒ - tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ $$\frac{1}{3}$$ - $$\frac{π}{4}$$

⇒  tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ 1 - tan$$^{-1}$$ $$\frac{1}{3}$$   [Since, $$\frac{π}{4}$$ = tan$$^{-1}$$ 1]

⇒ tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ $$\frac{1 - \frac{1}{3}}{1 + 1 • \frac{1}{3}}$$

⇒ tan$$^{-1}$$ $$\frac{1}{x}$$ = tan$$^{-1}$$ ½

⇒ $$\frac{1}{x}$$  = ½

⇒ x = 2

Therefore, the required solution is x = 2.

Inverse Trigonometric Functions

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

Recent Articles

1. Subtracting Integers | Subtraction of Integers |Fundamental Operations

Jun 13, 24 02:51 AM

Subtracting integers is the second operations on integers, among the four fundamental operations on integers. Change the sign of the integer to be subtracted and then add.

2. Properties of Subtracting Integers | Subtraction of Integers |Examples

Jun 13, 24 02:28 AM

The properties of subtracting integers are explained here along with the examples. 1. The difference (subtraction) of any two integers is always an integer. Examples: (a) (+7) – (+4) = 7 - 4 = 3

3. Math Only Math | Learn Math Step-by-Step | Worksheet | Videos | Games

Jun 13, 24 12:11 AM

Presenting math-only-math to kids, students and children. Mathematical ideas have been explained in the simplest possible way. Here you will have plenty of math help and lots of fun while learning.

4. Addition of Integers | Adding Integers on a Number Line | Examples

Jun 12, 24 01:11 PM

We will learn addition of integers using number line. We know that counting forward means addition. When we add positive integers, we move to the right on the number line. For example to add +2 and +4…